2005
DOI: 10.1007/s00347-005-1199-1
|View full text |Cite
|
Sign up to set email alerts
|

AB0-Blutgruppenexpression in Hornhäuten mit Transplantatversagen

Abstract: The results of this study show that ABO blood group antigens can be up-regulated in cases of corneal allograft failure, especially in cases of immune mediated graft rejection. This phenomenon might play a role in corneal allograft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…7 When literature is reviewed, various studies can be found on the relations between optic disorder and blood groups. [8][9][10][11][12] However, no previous study was found related to the effects of blood groups on VEP test.…”
Section: Introductionmentioning
confidence: 99%
“…7 When literature is reviewed, various studies can be found on the relations between optic disorder and blood groups. [8][9][10][11][12] However, no previous study was found related to the effects of blood groups on VEP test.…”
Section: Introductionmentioning
confidence: 99%